Direct and selective hydrogenolysis of arenols and aryl methyl ethers - Kusumoto, Shuhei; Nozaki, Kyoko (Nature communications, 2015)
For valorization of biomass, the conversion of lignin to deoxygenated bulk aromatic compounds is an emerging subject of interest. Because aromatic rings are susceptible to metal-catalysed hydrogenation, the selective hydrogenolysis of carbon–oxygen bonds still remains a great challenge. Herein we report direct and selective hydrogenolysis of sp 2 C–OH bonds in substituted phenols and naphthols catalysed by hydroxycyclopentadienyl iridium complexes. The corresponding arenes were obtained in up to 99% yields, indicating the possible production of arenes from lignin-derived bio-oils. Furthermore, the same catalysts were applied to the unprecedented selective hydrogenolysis of the sp 3 C–O bonds in aryl methyl ethers. Thus, the hydrodeoxygenation of vanillylacetone, a lignin model compound, afforded alkylbenzenes as the major products via triple deoxygenation. Deoxygenating phenols is a difficult task, made more complex by the tendency of hydrogenation techniques to also reduce the aromatic ring. Here, the authors show an iridium catalyst that can selectively cleave the C–O bond in phenols and related compounds, as well as cleaving aryl methyl ethers.